Analysis and phytochemical profile of Amaranthus tricolor L. extract with antioxidative and antimicrobial properties - Yang, Jinfeng; Kim, Myong Jo; Kwon, Yong Soo; Chen, Weiling; Yin, Feilong (Food Science and Technology, 2023)
Amaranthus tricolor L. is a cultivated green vegetable, commonly known as amaranth, which is similar to spinach, broccoli, and cabbage. In the present study, we investigated the antioxidant and antimicrobial activities of the methanol extract and various fractions from A. tricolor. Results show that A. tricolor ethyl acetate (EtOAc) extract displayed the highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging activity (IC50=16.43±1.53 μg/ml), which was higher than that of the positive control, butyl hydroxy anisd (IC50=19.42±0.91 μg/ml). This extract had a reducing power of 2.743 at 0.5 mg/ml and significantly attenuated production of reactive oxygen species in a dose-dependent manner. Further bioassay-monitored fractionation of the EtOAc extract yielded two flavonoids, kaempferol (1) and quercetin (2), and one phenolic acid, gallic acid (3). We found that the antimicrobial activity of compound 3 (at a dose of 63 μg/mL) was superior to that of the tetracycline control (at a dose of 250 μg/mL) against Escherichia coli. Additionally, compounds 1 and 2 (at a dose of 63 μg/mL each) displayed higher activities against Penicillium oxalicum and Staphylococcus aureus than the control. These results suggest that A. tricolor extract may represent a promising nutraceutical source due to the antioxidant and antimicrobial properties of its phenolic compounds.